Coordination mechanism design in supply chains using multi-behaviour agents. (19th July 2010) - Forget, Pascal; D'Amours, Sophie; Frayret, Jean-Marc; Gaudreault, Jonathan
In today's industrial context, competitiveness is closely associated with supply chain performance. The ongoing development of integrated supply chains has increased the importance of supply chain management. This paper focuses on the design of coordination mechanisms that determine how partners interact to coordinate their production planning. We present a simulation tool to aid in the design of coordination mechanisms using multi-behaviour agents in an agent-based planning system where agents act as partners. The implementation of this solution is realised through the FORAC agent-based planning platform, which is dedicated to supply chain production planning and simulation for the lumber industry.